2002
DOI: 10.5694/j.1326-5377.2002.tb04728.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn hearing screening in Western Australia

Abstract: Aim:To report the preliminary findings of a pilot program to screen newborn babies for congenital bilateral permanent hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…The pass rate for TEOAEs of 97% among non-Aboriginal children in our study is consistent with the pass rate of a newborn hearing screening in Perth, WA, in which the pass rate was 99% following assessment soon after birth and a repeat test if the baby failed the first time [23]. To our knowledge there are no published studies that have measured OAEs with comparable study design in healthy young non-indigenous children after the early neonatal period.…”
Section: Discussionsupporting
confidence: 86%
“…The pass rate for TEOAEs of 97% among non-Aboriginal children in our study is consistent with the pass rate of a newborn hearing screening in Perth, WA, in which the pass rate was 99% following assessment soon after birth and a repeat test if the baby failed the first time [23]. To our knowledge there are no published studies that have measured OAEs with comparable study design in healthy young non-indigenous children after the early neonatal period.…”
Section: Discussionsupporting
confidence: 86%
“…Using this modified protocol, the coverage rate was found to be high at 98.91%, meeting the recommended coverage by the Joint Committee of Infant Hearing (JCIH) [20], and was similar to the coverage rate observed for an obstetric hospital downtown (98.85%), where the majority of expectant mothers were residents [21]. The positive rate of 27.22% for hearing anomalies observed after the first hearing screening in the present study was much higher than that reported previously in several studies [21-24]. One study indicated that OAE testing had a 15.6% false positive rate in the first 24 hours of life, but this fell to 4% by 72 hours [22].…”
Section: Discussionsupporting
confidence: 87%
“…Although rescreening tests are the most important method for decreasing the false positive and referral rates, low rescreening rates have generally been a problem in newborn hearing screening programs [24,28,29], and even more so for frequent migrants. Our study shows that it is feasible and practical to achieve high coverage rates for screening for hearing loss and decrease the referral rates in newborn babies of migrant workers, using a modification of the currently employed UNHS protocol.…”
Section: Resultsmentioning
confidence: 99%
“…25 The effectiveness of many programmes in the United States has been limited by poor rates of screening and attendance for rescreen and for audiology evaluation after ''no clear response'' on UNHS. A study in Rhode Island, the first state in the United States to establish a state wide programme of UNHS, has shown that this is heavily dependent on socioeconomic and demographic variables: those with traditional Medicaid insurance were less likely to be screened or to be rescreened.…”
Section: Accuracy Of Unhs As Assessed In Infancymentioning
confidence: 99%